IDENTIFIKASI PERAN MANAJEMEN DALAM PROGRAM BIMBINGAN KELOMPOK, KLASIKAL, DAN LINTAS KELAS - Tiffada Islamic Laksmana; Aiuningtyas Yuni Oetari; Giralda Aufadzatul Hanan Akhmad; Elisabeth Christiana (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2026)
Guidance and counseling are assistance services provided for counselees or students and are provided both for individuals and groups to achieve certain goals and develop optimally in personal, social, learning, and career fields. Management is a process that includes planning, organizing, implementing, and controlling in carrying out an activity or program process, which has the aim of controlling the implementation of an event or program from start to finish. As is the case with guidance and counseling programs that require management in its implementation, a complex program makes management indispensable in it to control and structure the program so that it is planned, and runs well in accordance with the objectives of the program formed. The guidance and counseling program that will be discussed includes group, classical, and cross-class guidance programs. Guidance programs that do not only run for one individual but more than individual units and more than group units, therefore management takes a very important role in the implementation of the program. This research aims to identify the role of management in the implementation of guidance and counseling programs, especially in group, classical, and cross-class guidance programs. The method used in this research is qualitative with literature review techniques with a focus on management and group, classical, and cross-class guidance programs. The results obtained in this study show that there is an important role in management in the implementation of classical guidance programs with a focus on group, classical, and cross-class guidance.